Health issues in women and girls affected by haemophilia with a focus on nomenclature, heavy menstrual bleeding, and musculoskeletal issues. (6th May 2022) - Weyand, Angela C.; Sidonio, Robert F.; Sholzberg, Michelle
Abstract: Introduction: Women and girls affected by haemophilia, including haemophilia carriers (WGH) are at risk of bleeding symptoms that may go unrecognized, including heavy menstrual bleeding (HMB) and musculoskeletal bleeding. Terminology continues to evolve. Aim: To describe the current recommendations for nomenclature surrounding WGH, and the current understanding of HMB, iron deficiency, and musculoskeletal complaints in these patients. Methods: Literature was reviewed and summarized. Results: With regards to nomenclature, women with factor levels less than 50% should be classified as having haemophilia, while carriers with normal levels should be characterized accordingly to symptomatology. HMB and resultant iron deficiency are common among WGH, have a multitude of downstream effects, and maybe overlooked due to stigma around menstruation. Musculoskeletal bleeding and resultant joint changes are increasingly recognized in this population but do not necessarily correlate with factor levels. Conclusion: Although progress has been made in the care of WGH, much work remains to further improve their care. Abstract :